Digital Storytelling Melalui Media Sosial dalam Aktivitas Kehumasan Pada Perguruan Tinggi Alih Status - Yuliani Widianingsih; Intan Putri Cahyani (CHANNEL: Jurnal Komunikasi, 2020)
Transferring the status from a private university to a state university makes the Universitas Pembangunan Nasional Veteran Jakarta has more responsibility in the management and governance of communication. Therefore available social media as PR tools that can be reached by all stakeholders is significant. As an institution engaged in education, UPN Veteran Jakarta is active in using social media and has even made achievements. In PR activities of UPN Veteran Jakarta as the new state university through social media, the form of communication is carried out in the form of the use of stories or narratives combined with various elements or known as digital storytelling. Therefore, researchers are interested in researching digital storytelling through social media at UPN Veteran Jakarta as a university that is experiencing a status change. This type of research is a qualitative descriptive using the case study method. The object of research is focused on digital storytelling on the activities of all social media accounts owned by UPN Veteran Jakarta. The research data collection was carried out through (1) observation in the form of daily monitoring of the activities of all social media, (2) interviews with leaders and PR staff of UPN Veteran Jakarta. The study found that digital storytelling is a new way of building and maintaining brand reputation, spoken-content is the main key in digital storytelling, and social media makes digital storytelling more powerful and impactful.